2009
DOI: 10.1002/app.30603
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors affecting synthesis of polyvinyl butyral by Taguchi method

Abstract: Polyvinyl butyral (PVB) was prepared by condensation reaction of butyral with polyvinyl alcohol (PVA) in aqueous phase containing an acid as a catalyst and an emulsifying agent. Properties of the polymer were a function of the relative amounts of the three randomly distributed units of acetal, acetate and vinyl alcohol groups, and the molecular weight. In this work, some effective factors in synthesis of PVB have been investigated by Taguchi method. The percent of the acetalization has been determined accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…electrode material, in electrochemical energy storage [9], as a catalyst support in fuel cells [10], in supercapacitors [11] and in solar cells [12].…”
Section: -2506mentioning
confidence: 99%
See 1 more Smart Citation
“…electrode material, in electrochemical energy storage [9], as a catalyst support in fuel cells [10], in supercapacitors [11] and in solar cells [12].…”
Section: -2506mentioning
confidence: 99%
“…For example, a study by Hajian et al [12] applied the Taguchi method to investigate several factors in the synthesis of polyvinyl butyral. Another study by Shahbazian et al [1] reported the influence of five operating variables on the polymerization of vinyl chloride using the Taguchi method.…”
Section: -2506mentioning
confidence: 99%
“…It is a low-cost alternative that offers strong binding ability, flexibility, optical clarity, and adhesion to many surfaces. 4 The balance of hydroxyl groups and butyral rings in the PVB structure, which depends on the reaction conditions and can be represented by the degree of acetalization, is critical to determine the final properties and applications of the copolymer. 2,3 PVB, which chemical structure is schematically shown in Figure 1, is a random thermoplastic copolymer obtained by the acetalization reaction between poly(vinyl alcohol) (PVA) and butyraldehyde (BU) in acidic medium.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of applications of PVA and its derivatives can be found in several fields, in particular for the development of biomedical, cosmetic, textiles, paper, and adhesives. [46][47][48][49] Several other aldehydes have been grafted on PVA [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] and poly(vinyl acetals) have been utilized, among others, to obtain Langmuir-Boldgett films, 50,51 membranes for ultrafiltration, 66 fluorescent polymers for biomedical uses, 67 or anti-corrosions agents for material science. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Thus, PVA acetalization with aldehydes has also been reported 45 and some of the resulting poly(vinyl acetals) are commercially available.…”
Section: Introductionmentioning
confidence: 99%